Proposta de atividades experimentais em educação ambiental para conteúdos do 1º ano do ensino médio com a utilização de protótipos de filtro de carvão ativado de caroços de açaí (Euterpe oleracea) - (:unkn) unknown (Brasil, 2020)
Açaí seeds are quite abundant in the municipality of Macapá, among others, constituting residues from the local açaí juice production industry, this residue can be transformed into activated carbon and used as an adsorbent for mixture separation processes. On the other hand, much knowledge about these concepts is little explored in textbooks, which rarely present proposals for experimentation and contextualization in the classroom. This work aims to contribute in this sense, in this way, at the first moment, the manufacture and activation of charcoal from açaí stones was made, subsequently making two prototypes of filters that can be used for educational purposes. In the second moment, analyzes were carried out in didactic books in order to verify how concepts are being approached, related to the contents of substances, phases (mixtures) and separation of mixtures, taking into account the contextualization and practical experimentation, and later on, for proposing practical class methodologies. and experimental ones that can be used by teachers and researchers, to plan and execute inventions in the classroom. The results showed the feasibility of using the activated carbon of açaí as an adsorbent agent in the process of filtration and separation of mixtures, in addition to pointing out that the explored concepts are little used in textbooks in order to propose practical and experimental activities in the classroom, that allow the student to internalize the concepts passed on in the best way. The work is important, as it proposes practical interventions through elements of local daily life and low-cost materials, which can be applied even in schoolchildren with few or no resources for the development of pedagogical activities.
Keywords: Açaí - caroço; Educação ambiental - atividade experimental; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA